The Proficiency Levels Of Bahasa Melayu Writing Skills In Malaysian Primary Schools. - Othman, Hashim; Mohamed, Abdul Rashid; Mohamed Ismail, Shaik Abdul Malik; Ahmad, Halim (USM, 2006)
The 1996 Education Act affirms the status of Bahasa Melayu as a language of knowledge and as a medium of instruction in national schools in Malaysia (Education Act, 1996; Sharifah Maimunah, 2004). Correspondingly, by the end of their primary education pupils are expected to acquire a certain level of Bahasa Melayu proficiency that will enable them to grasp lessons conducted in Bahasa Melayu at the secondary school and tertiary levels.